President, Kinship Politics, and Election 2019, and Its Influence on Regional Head Elections 2020 in Surakarta - M Saidi Rifki; Mujaeni (Ministry of Home Affairs, 2021)
This research departs from the victory of President Joko Widodo's son and son-in-law in the 2020 Regional Head Election. Approximately 44% or 55 candidates of the 124 regional head candidates who have a kinship with the authorities are confirmed to win the 2020 simultaneous Regional Head Election and stroll as regional heads. For this reason, this study will explore the phenomenon of winning candidates exposed to kinship politics, especially with the president in the 2020 Regional Head Election. This research also analyzes some of the causes of nepotism in the democratic system that are still visible in the 2020 simultaneous Regional Head Election. To achieve this goal, the research uses descriptive research methods with a qualitative approach. The method was chosen because the 2020 simultaneous Regional Head Election were multidimensional. The results of the study found several factors that led to kinship politics still coloring the 2020 Regional Head Election, including the advancement of candidates who were exposed to kinship with the president. These factors, such as the popularity of family names, are deliberately carried out by politicians as a way of inheriting power and the weak democratization of political parties, such as recruiting candidates for the regional head. This also led to candidates exposed to kinship with the president in striding to win the Regional Head Election. This research concludes that kinship should be able to lead to moral behavior, not just a pursuit of power. Concerning kinship politics, it can be controlled through internal reforms of political parties as institutions that carry out the role of candidate recruitment.